Adult idiopathic jejuno-ileal intussusception - Nkwam, N (BMJ Publishing Group, 2010)
This 67-year-old woman, with numerous previous abdominal operations, presented to her general practitioner 3 years ago with generalised abdominal pain and diarrhoea. With unremarkable haematology tests and a CT scan at that time she was given the diagnosis of irritable bowel syndrome. During the next 3 years her symptoms continued intermittently and now associated with vomiting and weight loss. This time both a barium follow-through followed by a CT scan demonstrated a small bowel intussusception. A laparotomy was done but surprisingly no intussusception was found, only a single adhesional band which was divided. She was discharged 5-days postoperative but re-admitted 3 days later with abdominal discomfort, bloating and vomiting. A repeat CT scan again showed the presence of a small bowel intussusception and a second laparotomy was performed, this time demonstrating a jejuno-ileal intussusception which was reduced and resected with primary anastomosis. Her postoperative course was without incidents.